ELDERLY WOMEN’S LEADING ROLE IN REPORTING VIOLENCE: A GROUNDED THEORY - Damaceno, Daniela Garcia [UNESP]; Sanches Alarcon, Miriam Fernanda; Chirelli, Mara Quaglio; Lazarini, Carlos Alberto; Sanches Marin, Maria José (FapUNIFESP (SciELO), 2024)
Objective: to interpret the experience of empowering elderly women to report domestic violence and develop a theoretical model that explains it. Method: a qualitative study, carried out using Grounded Theory. Between February 2018 and January 2020, semi-structured interviews were conducted with 21 elderly women who filed police reports. Also, nine professionals working at the Women’s Defense Station of the Civil Police of the State of São Paulo, Brazil, located in a medium-sized city in the countryside of São Paulo, were interviewed. Results: the phenomenon identified as “Taking the lead in coping with violence”, based on the categories, revealed that elderly women experience multiple conditions of vulnerability resulting from the situation of dependency, conflicts in relationships and unfavorable living conditions. Even so, the impacts of this violence generate the need to take action against it and to be empowered to report it. After reporting it, they experience the complexity of it and find ways to deal with the situation. Conclusion: violence reporting by elderly women derives from the individual empowerment process, driven by the decision to stop the abuse, even with possible consequences, thus awakening critical awareness based on self-perception of the context of life.
EL PAPEL PROTAGÓNICO DE LAS MUJERES MAYORES EN LA DENUNCIA DE VIOLENCIA: UNA TEORÍA FUNDAMENTADA
O PROTAGONISMO DE MULHERES IDOSAS NA DENUNCIA DA VIOLENCIA: UMA TEORIA FUNDAMENTADA
Keywords: Aging; Elder abuse; Empowerment; Mandatory reporting; Notification; Violence against women